Ultrahigh field MR imaging of a subconjunctival anti-glaucoma drug delivery system in a rabbit model. Issue 1 (December 2017) - Kopp, Franziska; Eickner, Thomas; Polei, Stefan; Falke, Karen; Witt, Martin; Grabow, Niels; Stachs, Oliver; Guthoff, Rudolf; Lindner, Tobias
Abstract Local drug delivery systems (DDS) have become a favourable approach for the treatment of numerous diseases. Biomedical imaging techniques such as ultrahigh field magnetic resonance imaging (UHF-MRI) offer unique insight into DDS biodegradationin vivo . We describe the establishment of a 7 Tesla MRI routine for longitudinalin vivo examinations of a subconjunctival DDS for the treatment of glaucoma in a rabbit model. In initialin vitro examinations the T2-relaxation times of the polymeric DDS components were assessed. Imaging of enzymatically degraded depot samplesin vitro did not reveal changes in sample morphology or T2-relaxation time.Ex vivo investigations with an enucleated porcine eye showed good correlation of anatomical MRI and histological data. In longitudinalin vivo studies in rabbits, we repeatedly scanned the depot in the same animal over the course of 5 months with an in-plane resolution of 130 µm at scan times of less than 30 minutes. The degradation was quantified using volumetric analysis showing a volume reduction of 82% between 3 and 21 weeks after depot implantation. We have thereby demonstrated the feasibility of our UHF-MRI protocol as a non-invasive imaging routine for qualitative and quantitative, longitudinal evaluation of biodegradable subconjunctival DDS.